Understanding the Lived Experiences of Hispanic Sexual Minority Youth and their Parents - Lozano, Alyssa; Fernández, Alejandra; Tapia, Maria I.; Estrada, Yannine; Juan Martinuzzi, Lara; Prado, Guillermo (Family process, 2021)
Disclosure of sexual identity and/or gender orientation is difficult for youth and is associated with elevated adverse health risks, particularly when there is parental rejection. There are limited studies conducted with Hispanic sexual minority youth (HSMY) and their families to understand the disclosure process, how the family unit changes and adapts following disclosure, and the implications for preventive interventions for HSMY and their families. This paper explores the lived experiences of youth and parents throughout the disclosure process. A phenomenological approach was used to interview 15 parent–youth dyads (N = 30) to understand what it means for Hispanic youth to disclose their sexual identity and/or gender orientation. Three themes that best described the experience emerged from the participant interviews; the experience of disclosing included intrapersonal challenges, navigating disclosure, and conceptualizing acceptance. The authors highlight implications for preventive interventions that can help these families undergoing the unique process of disclosure. Resumen La revelación de la identidad sexual o la orientación de género es difícil para los jóvenes y está asociada con riesgos adversos elevados para la salud, particularmente cuando existe rechazo por parte de los padres. Se han realizado pocos estudios con jóvenes de minorías sexuales hispanas y sus familias para comprender el proceso de revelación, cómo el núcleo familiar cambia y se adapta después de la revelación, y las consecuencias para las intervenciones preventivas orientadas a los jóvenes de minorías sexuales hispanas y sus familias. En este artículo se analizan las experiencias vividas de los jóvenes y sus padres a lo largo del proceso de revelación. Se utilizó un método fenomenológico para entrevistar a 15 díadas de padres y jóvenes (N = 30) a fin de comprender qué significa para los jóvenes hispanos revelar su identidad sexual o su orientación de género. De las entrevistas a los participantes surgieron tres temas que describieron mejor la experiencia; la experiencia de la revelación incluyó desafíos intrapersonales, el paso por la revelación y la conceptualización de la aceptación. Los autores destacan las implicancias para las intervenciones preventivas que pueden ayudar a estas familias a atravesar el proceso único de la revelación. 摘要 对青少年来说，公开自己的性身份和/或性别取向是困难的，而且特别是当父母拒绝接受这些说出的性取向情况时，有损健康的风险就会增加。以了解公开过程、公开后家庭单位如何变化和适应，以及对HSMY及其家庭的预防干预的影响等等为研究目的的，针对西班牙裔性少数群体青少年(HSMY)及其家庭的研究并不多。本文旨在探讨青少年和父母在身份揭露过程中的切实生活经历。本研究采用现象学的方法，对15对父母与青少年(N = 30)进行访谈，以了解西班牙裔青少年公开他们的性认同和/或性别取向意味着什么。参与者访谈中出现了三个最能描述这种经历的主题；披露的经历包括个人内在的挑战、公开过程引导和概念化接受。作者强调了预防性干预措施的意义，这些措施可以帮助这些正在经历独特的披露过程的家庭。